2021
DOI: 10.1007/s11606-021-07106-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Capacity Strain: a Qualitative Analysis of Experience and Solutions at 13 Academic Medical Centers

Abstract: Background Hospital capacity strain impacts quality of care and hospital throughput and may also impact the well being of clinical staff and teams as well as their ability to do their job. Institutions have implemented a wide array of tactics to help manage hospital capacity strain with variable success. Objective Through qualitative interviews, our study explored interventions used to address hospital capacity strain and the perceived impact of these interventions, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(46 reference statements)
0
24
0
Order By: Relevance
“…A reflexive approach for hospitals to improve costs and efficiency may be to “squeeze more juice out of the lemon” (i.e., encourage hospitalists to see more patients more quickly). Preliminary studies suggest, however, that increasing clinical workloads negatively impact hospitalist well‐being, mental health, and hospitalist job performance, 2,3,5 while simultaneously negatively impacting hospital operational and financial outcomes 5,6 …”
Section: The Trade‐offs Of Productivitymentioning
confidence: 99%
See 4 more Smart Citations
“…A reflexive approach for hospitals to improve costs and efficiency may be to “squeeze more juice out of the lemon” (i.e., encourage hospitalists to see more patients more quickly). Preliminary studies suggest, however, that increasing clinical workloads negatively impact hospitalist well‐being, mental health, and hospitalist job performance, 2,3,5 while simultaneously negatively impacting hospital operational and financial outcomes 5,6 …”
Section: The Trade‐offs Of Productivitymentioning
confidence: 99%
“…Increasing workloads affect hospitalist job performance, such as perceived quality of care and operational outcomes (e.g., length of stay). Studies have shown that 40% of physicians stated that their typical patient load in the inpatient setting exceeded safe levels at least monthly 10 and that resources often lag behind the ever‐increasing workloads 3 . Another study by Elliott et al 5 highlighted that when physicians saw more than 15 patients in a shift, patient length of stay increased exponentially and costs increased (i.e., hospital charges).…”
Section: The Trade‐offs Of Productivitymentioning
confidence: 99%
See 3 more Smart Citations